Implementation of the Prosecution Process in the Criminal Justice System at the Attorney General's Office - Aras Firdaus (Veteran Law Review, 2022)
The Prosecutor's Office as one of the law enforcement agencies is required to play a greater role in enforcing the law, protecting the public interest, enforcing human rights, and eradicating corruption, collusion and nepotism. The Prosecutor's Office is the only government agency implementing state power that has duties and authorities in the field of prosecution in law enforcement and justice in the general court environment. This study is to determine the criminal justice system in prosecution in Indonesia, how the criminal justice system in the application of prosecution in Indonesia and How is criminal responsibility as a criminal justice system through prosecution by the prosecutor. The research method uses normative juridical. The results of the study show that the prosecution system must be guided by the principles adopted by countries in the world as the basis for prosecuting. These principles are the principle of legality and the principle of opportunity. Prosecutors are carried out by public prosecutors, and public prosecutors are prosecutors who are authorized by this law to carry out prosecutions and carry out judges' decisions. The conclusion of the study is that the Prosecutor's Office of the Republic of Indonesia as part of the judicial power is pure and free from the intervention of political power by including the Prosecutor's Office of the Republic of Indonesia explicitly in the articles in the 1945 Constitution of the Republic of Indonesia or by revising Law No. 16 of 2004 concerning Attorney.. The crime committed by the suspect will be reviewed by the public prosecutor, the public prosecutor has full authority in carrying out the prosecution. Suspected perpetrators of criminal acts will enter the criminal justice system when there is an arrest and then detained and brought to court so that they can be officially prosecuted.Keywords:Prosecutor; criminal justice; attorney